Defect Segregation and Its Effect on the Photoelectrochemical Properties of Ti-Doped Hematite Photoanodes for Solar Water Splitting - Scherrer, Barbara; Li, Tong; Tsyganok, Anton; Doebeli, Max; Gupta, Bhavana; Malviya, Kirtiman Deo; Kasian, Olga; Maman, Nitzan; Gault, Baptiste; Grave, Daniel A.; Mehlman, Alexander; Visoly-Fisher, Iris; et al. (Chemistry of Materials, 2020)
Optimizing the photoelectrochemical performance of hematite photoanodes for solar water splitting requires better understanding of the relationships between dopant distribution, structural defects, and photoelectrochemical properties. Here, we use complementary characterization techniques including electron microscopy, conductive atomic force microscopy (CAFM), Rutherford backscattering spectroscopy (RBS), atom probe tomography (APT), and intensity-modulated photocurrent spectroscopy (IMPS) to study this correlation in Ti-doped (1 cat. %) hematite films deposited by pulsed laser deposition (PLD) on F:SnO2 (FTO)-coated glass substrates. The deposition was carried out at 300 °C followed by annealing at 500 °C for 2 h. Upon annealing, Ti was observed by APT to segregate to the hematite/FTO interface and into some hematite grains. Since no other pronounced changes in microstructure and chemical composition were observed by electron microscopy and RBS after annealing, a nonuniform Ti redistribution seems to be the reason for reduced interfacial recombination in the annealed films, as observed by IMPS. This results in a lower onset potential, higher photocurrent, and larger fill factor with respect to the as-deposited state. This work provides atomic-scale insights into the microscopic inhomogeneity in Ti-doped hematite thin films and the role of defect segregation in their electrical and photoelectrochemical properties.
CRIS-Team Scopus Importer:2023-03-07